(untitled) (Actualizaciones en Sida e Infectología, 2025)
Respiratory infections in immunocompromised patients present a significant diagnostic and therapeutic challenge. This case describes an unusual triple respiratory coinfection involving Lophomonas spp., Coccidioides immitis, and Bordetella pertussis in a patient with chronic kidney disease on hemodialysis. The investigation emphasizes the importance of considering epidemiology, radiological findings, and microbiology for accurate diagnosis in non-specific clinical presentations. It highlights the critical need for a multidisciplinary diagnostic approach in immunocompromised patients with rare respiratory infections to achieve successful treatment.